(untitled) (Al-Qamar, 2021)
Allah the Almighty has sent around 124000 Messengers in this world to edify and guide humanity. All these Messengers were sent for a short span of time and for particular nations. These Messengers preach the Divine message and guide the mankind according to the needs of that time. Muhammad (PBUH) is the last and final Messenger and Prophet of Allah in this world. He was sent with Last Divine book and ultimate religion towards all humanity. His teachings and guidance are source of guidance for all humanity till the Day of Judgment. Islam is not merely a religion but a complete code of life that provide Divine guidance regarding each and every aspect of human life. Islam provides the Divine solution of every problem of human beings. Islam has also provided ample guidance that how to deal the situation of famine and pandemics in all times. In this article the rulings of Islam regarding epidemics and pandemics will be elaborated in the light of the Quran, teachings of the Holy Prophet PBUH and the actions of Rightly Guided Caliphs.